Coseismic DInSAR Analysis of the 2020 Petrinja Earthquake Sequence - Magyar, Bálint (Periodica Polytechnica Civil Engineering, 2022)
Interferometric SAR analysis provides an excellent opportunity to perform large-scale and rapid coseismic deformation mapping. Between December 28-30, 2020, three earthquakes with magnitudes greater than 4.3 occurred during the 2020 Petrinja Earthquake Sequence near Petrinja in Croatia, resulting in significant coseismic deformation. Considering both the available ascending and descending Sentinel-1A/B images preceding and following the Petrinja Earthquake Sequence, 2.5D differential interferometric analysis was performed to determine the resulting deformation field, which have significant importance in civil engineering related countermeasures and hazard assessment. With the applied methodology, the derived horizontal and vertical deformation fields can be characterized by a maximum of ±0.43 m local East-West, a maximum of 0.15 m local subsidence and a maximum of 0.19 m local vertical uplift near Petrinja.